Ionogel-based solid-state supercapacitor operating over a wide range of temperature. (10th July 2016) - Negre, L.; Daffos, B.; Turq, V.; Taberna, P.L.; Simon, P.
Abstract: An inorganic gel polymer electrolyte based on the confinement of an ionic liquid mixture (1:1 by weight or molar ratio) of N-methyl-N-propylpiperidinium bis(fluorosulfonyl)imide (PIP13FSI) and N-butyl-N-methylpyrrolidinium bis(fluorosulfonyl)imide (PYR14FSI) into a SiO2 matrix prepared from a sol-gel method was prepared and further used as electrolyte in an all solid-state supercapacitor. The synthetized ionogel exhibits a high ionic conductivity over a wide temperature range (from 0.2 mS cm −1 at −40 °C up to 10 mS cm −1 at 60 °C). The ionogel-based supercapacitor using two activated carbon electrodes can be operated over 3 V cell voltage window. Moreover this all solid-supercapacitor shows a capacitance up to 90 F g −1  at room temperature. These encouraging results show the interest of developing such devices, including non-toxic and safer electrolytes, packaging issues and flexible devices development.